Fatores de risco para coronariopatia em pacientes com diabetes mellitus tipo 2 atendidos no Hospital Universitário joão de Barros Barreto - LADEIRA, Suzanny Silva (2022)
Diabetes mellitus increases the sensitivity for atherosclerosis giving to these patients a relative risk of death for coronary arterial disease (CAD) about three times bigger than for the population in general. Objective: To establish the association between cardiovascular risk factors and the presence of CAD in type 2 diabetics assisted in the Hospital Universitário João de Barros Barreto (HUJBB) and identify the cardiovascular risk in 10 years through the Framingham Risk Score (FRE). Casuistic and Methods: An observational and transversal study with 112 patients with type 2 diabetes assisted in the ambulatories of endocrinology, cardiology and medical clinic of the HUJBB between September and February (2007/2008). A form was prepared for getting the informations about the personal and economical data, presence of CAD, interest risk factors (diet, sedentary life, smoking, etilism, pressoric levels, dyslipidemias, BMI, waist circumference, glucose levels, familiar history) and FRE. Were considered CAD + all of those who are in treatment for coronary disease, myocardial cintilography with perfusion abnormalities, prior heart attack, "stent", angioplasty and revascularization. The processing and analysis of the data were done through the programs Word and Excel 2003, Bioestat 3.0 and Epi-info 2000. In the statistical analysis, the tests used were Chi-square, Mann-Whitney and Z test according to the characteristics of the variables. The significance level adopted was p ≤ 0,05. The project was valued and approved by the Ethics in Research Commission with Human of the HUJBB/UFPA. Results: The studied population had average of 58 years and was composed mainly by women (55,4%); brown (69,6%); married (58,0%); inactive (57,1%) and individuals with low degrees of education (54,4%) and income (71,4%). In this sample, 44 patients had CAD (39,3 %). The demographic characteristics associated to DAC were age, occupation and income (p ≤ 0,05). According to the life style, the patients with coronary disease presented bigger frequency of unsuitable diets (77,3 % vs 63,2 %; p = 0,17), sedentary life (90,9 % vs 73,5 %; p = 0,04) and smoking (prior or current) (61,4 % vs 47,1 %; p = 0,03) and less frequency of etilism (4,5 % vs 7,4 %; p = 0,54). The personal antecedents of HBP (high blood pressure), dyslipidemias and obesity were more prevalent among CAD +, 84,1%, 84,1% and 40,9% respectively, meantime, only HBP was correlated significantly with the CAD (p = 0,02). The values of SBP and DBP were lifted up in the individuals CAD – as much as in the CAD +, with bigger predominance on the last ones (p > 0,05). Diabetics with CAD exhibited higher levels of CT (56,8%), LDL-c (77,3%) and TGC (47,7%) and those without CAD of HDL-c (30,9%), however the serum levels of the lipids didn’t have association with the CAD (p > 0,05). The frequency of BMI ≥ 25 Kg/m² was 60,7% and of inadequated waist circumference was 78,4%, with a bigger frequency in the group with coronary disease (p ≤ 0,05). Glucose levels, fast blood glucose and glycohemoglobin were elevated in the same way in both groups (p > 0,05). Most of the individuals answered affirmatively for the presence of familiar records for cardiovascular disease (58,9%), HBP (75,0%), dyslipidemias (61,6 %) and DM 2 (72,3%), however any of this familiar antecedents had statistical signification (p > 0,05). In accordance with the FRE, there was a bigger number of patients with middle and high cardiovascular risk, with the biggest scores corresponded to the patients already CAD + (p = 0,02). Conclusion: In this study, age, occupation, income, sedentary life, smoking, personal antecedent of HBP, BMI and abdominal circumference were the risk factors that associated to the CAD (p ≤ 0,05), in the same way of the values obtained through the Framingham score (middle and high risk).